Brine spill remediation utilizing capillary transport and wicking materials in loam and silty clay soils. Issue 1 (10th January 2022) - Green, Aaron W.; DeSutter, Thomas M.; Meehan, Miranda A.; Daigh, Aaron L. M.
Abstract: Oil and gas extraction from the Bakken and Three Forks shale‐oil reserves often produces large volumes of highly saline water, or brine. Brine releases often cause soils to exhibit poor structural and edaphic properties. Because of these negative effects, active remediation is often attempted through the use of in‐situ and ex‐situ techniques. Unfortunately, many conventional methods can be time intensive, costly, and only partially effective. This study sought to determine if salts could be efficiently removed from coarse‐ and fine‐textured soils through the surficial application of a wicking medium consisting of an engineered, paper‐based humidifier wick or ground wheat ( Triticum aestivum L.) straw while soils were irrigated from the subsurface with either purified water or a gypsum solution. Over a 56‐d period, the humidifier wick with a gypsum solution reduced extractable Na by 82 and 23% in the loam and silty clay columns, respectively. The humidifier wick with purified water treatments reduced extractable Na by 77 and 8% in the loam and silty clay columns, respectively. Ground straw reduced extractable Na by <12% in all cases. The humidifier wick reduced the mean soil electrical conductivity (EC) by >9 dS m –1 with the largest reductions at deeper depths (i.e., >15 dS m –1 or >90% removal). Results show that evaporative wicks are comparable to other surficial remediation techniques in removing salt mass from soil. Core Ideas: Evaporative wicking materials are efficient at transporting water. Evaporative wicks can be an effective method to remove salts from soil. Saturated gypsum solution aids in Na removal and avoiding dispersion in clayey soils.